The default risk of UK real estate companies - Roditou, Liana (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
UK housing market, is facing for many years a history of booms and busts known as a “british disease”. The aim of this thesis is to examine financial and macroeconomic determinants in relation to the default risk of UK real estate market by applying a Probit accounting model in order to eliminate the causes of booms and busts of UK economy. The reason why the Logit regression model was not selected it its efficiency to observe the multivariate among the independent variables while the Probit is more efficient as the model has not fatter tails like Logit model. This study will examine UK companies’ indices as a case study by running the Probit regression model for justifying the initial hypothesis of failure. In addition, this study will investigate at which points the correlation, coefficient or significance level are high or low enough to cause issues based on 2-log likelihood and adjusted R square of the model summary. The initial hypothesis of failure can be obtained through the increase of CATA, which is the most suitable positive variable according to the overall outcomes. As well as, descriptive statistics of Size, Net Income and Debt Coverage for failed and non-failed firms will be illustrated were Altman’s model will be further discussed in the thesis as well as some recommendations and limitations.
Keywords: Financial determinants; Macroeconomic determinants; Real estate; Probit accounting model